PENGEMBANGAN TRAINER LANDSLIDE SMART MITIGATION (LSM) SEBAGAI EDUKASI MITIGASI DINI TANAH LONGSOR DI SMA NEGERI 1 PULUNG - Pratama, Handyesa Dika; Sulistiyo, Edy; Baskoro, Farid; Nurhayati, Nurhayati (Universitas Negeri Surabaya, 2021)
Improving the quality of education and learning activities in the aspect of disaster mitigation, educational institutions are an important means to help provide students with an understanding of the importance of natural disaster mitigation. Improving the quality of disaster mitigation education can be done by providing students with learning media to improve their understanding of mitigating natural disasters that will occur. The purpose of making trainers disaster mitigation as learning media is an effort to support students' understanding of the importance of natural disaster mitigation. The use of the research & development ADDIE method in this study aims to develop learning media to educate students about disaster mitigation. The data comparison process was carried out using the results of the pretest and posttest by analyzing the learning outcomes of 32 students of SMA Negeri 1 Pulung on geography subjects about landslide disaster mitigation using LSM trainer learning media. Development results Trainer landslide smart mitigation (LSM) obtained a level of validity with average score trainers of 90.54% for, job sheets 87.50% for, and 88.89% for questions, meaning that the research product is very valid to be implemented as a learning medium. Based on analysis of test for normality Kolmogorov-Smirnov gain score significance pretest 0.200 and score significance posttest 0.164 and the results of the t-test analysis obtained a score significance (2-tailed) is 0.000, so the trainer LSM, worksheets, and questions can be said to be effective as a means of support. The practicality of trainers LSM and job sheets are known from the answers to the questionnaire responses of 32 students with an average score of 84.76%, meaning that learning using trainers LSM and job sheets is very practical as a learning medium.